Faktor-Faktor yang Mempengaruhi Preferensi Muzaki dalam Membayar Zakat Secara Digital di Kota Banjarmasin - Tasya Oktavia Putri; Mairijani (P3M Politeknik Negeri Banjarmasin, 2024)
Technological advancements enable ease of access, including digital zakat payments without face-to-face interaction. Digitalization of zakat is necessary to enhance efficiency, effectiveness, and maximize the potential of zakat collected and distributed by Zakat Management Organizations (OPZ). This study aims to determine the influence of knowledge, ease of use, and trust on the preference of muzaki in paying zakat digitally in Banjarmasin City. This research employs a quantitative method with a descriptive approach. The population consists of 652.780 Muslim residents of Banjarmasin in 2023, with a sample size of 96 individuals. The sample size was calculated using the Slovin formula, with purposive sampling and data collection through questionnaires. The data analysis technique used is multiple linear regression analysis. The hypothesis testing results indicate that knowledge has a significant influence on the preference of muzaki tvalue (2,145) > ttable (1,986), ease of use has does not significant influence on the preference of muzaki tvalue (1,928) < ttable (1,986), and trust has a significant influence on the preference of muzaki tvalue (5,486) > ttable (1,986). Additionally, simultaneously, knowledge, ease of use, and trust have a positive influence on the preference of muzaki Fvalue (41,387) > Ftable (2,70). These three independent variables collectively contribute 56,1% to the dependent variable, which is the preference of muzaki.